Pengembangan Sistem Reservasi Ruang Laboratorium Berbasis Laravel 11 dengan Fitur Kalender Interaktif di STIKES Bhakti Husada Mulia Madiun - Muhammad Syafil Kafi Umar; Achmad Agus Athok Miftachuddin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to design and develop a Laravel 11-based Laboratory Space Reservation System with an Interactive Calendar Feature at STIKES Bhakti Husada Mulia Madiun. This system was built to address the problem of the manual laboratory loan process, which often causes schedule conflicts, late confirmations, and minimal documentation. The development method uses the Waterfall model which includes the stages of needs analysis, design, implementation, testing, and maintenance. The system was developed using Laravel 11 and a MySQL database, with testing using the Black Box method to ensure all functions run as needed. The implementation results show that the system is able to speed up the reservation process, improve data accuracy, and reduce the risk of schedule conflicts. This research is expected to be an effective digital solution in improving the efficiency and transparency of laboratory management in the health college environment.